Misalignment in Organic Waste Management Systems: A Review of Strategic and Institutional Failures in Indonesia - Akhmad Qosasih; Achmad Husen; Dian Alfia Purwandari; Danang Pratomo; Yeni Astuti (Jurnal Syntax Admiration, 2025)
Organic waste management is one of the main challenges in sustainable environmental development in Indonesia. Although waste sorting efforts have been encouraged at the household level, the reality is that there is still a remixing of organic and inorganic waste while in transportation facilities and in management units such as TPS and TPA. This study aims to systematically review the literature that discusses systemic failures in organic waste management, focusing on the strategic and institutional management aspects of waste management units. The method used is a systematic literature study of academic publications, policy reports, and relevant field studies in the period 2010–2024. The results of the study show that the mismatch between strategies at the upstream and downstream levels, the weak institution of TPS/TPA management, and the absence of incentive systems and results-based performance are key factors causing system inefficiency. This study recommends the need to redesign management strategies based on upstream-downstream integration, institutional strengthening of management units, and the application of performance measurement that encourages sustainable organic waste processing.